The Impact of Knowledge Sharing and Work Discipline on Village Officials' Performance in Jabon Subdistrict: The Mediating Role of Work Motivation - Muhammad Fatihul Iman; Sriyono Sriyono; Rita Ambarwati Sukmono (Yayasan Riset dan Pengembangan Intelektual, 2024)
Improving the performance of village officials can be achieved through the optimization of factors that influence it such as knowledge sharing, work discipline and high work motivation. This condition is important to realize excellent service for the community at the village level. This study aims to analyze the influence of knowledge sharing and work discipline on performance through the work motivation of village officials in Jabon District to provide recommendations for improving the performance of village officials and the quality of public services. This research uses a quantitative approach with a hypothesis testing design to explain the causal relationship between variables through statistical data analysis. Data were collected from 138 respondents through questionnaires, then their validity and reliability were analyzed and hypotheses were tested through multiple linear regression analysis using SEM PLS.